Zone refining of zirconium in an electric field - Kozhevnikov, O.E.; Pylypenko, M.M.; Stadnik, Yu.S.; Azhazha, R.V. (Вопросы атомной науки и техники, 2020)
The physical grounds and an experimental study of the efficiency of applying the zone recrystallization method in an electric field for zirconium refining from metal and gas-forming impurities are presented. The changes in the elemental composition, microhardness, and structure of the obtained ingots was investigated. It is shown that the application of the method can significantly reduce the content of interstitial impurities. Zirconium samples with a purity of 99.91 wt.% were obtained. Представлено фізичне обґрунтування та експериментальне дослідження ефективності застосування методу зонної перекристалізації в електричному полі для рафінування цирконію від металевих та газоутворюючих домішок. Досліджено зміни елементного складу, мікротвердості та структури одержуваних злитків. Показано, що застосування методу дозволяє значно знизити вміст домішок впровадження і отримати зразки цирконію чистотою 99,91 мас.%. Представлены физическое обоснование и экспериментальное исследование эффективности применения метода зонной перекристаллизации в электрическом поле для рафинирования циркония от металлических и газообразующих примесей. Исследованы изменения элементного состава, микротвердости и структуры получаемых слитков. Показано, что применение метода позволяет значительно снизить содержание примесей внедрения и получить образцы циркония чистотой 99,91 мас.%.